Primary familial brain calcification linked to deletion of 5' noncoding region of SLC20A2. (10th October 2016) - Pasanen, P.; Mäkinen, J.; Myllykangas, L.; Guerreiro, R.; Bras, J.; Valori, M.; Viitanen, M.; Baumann, M.; Tienari, P. J.; Pöyhönen, M.; Baumann, P.
Abstract : Objectives: Primary familial brain calcification (PFBC) is a rare neurological disease often inherited as a dominant trait. Mutations in four genes ( SLC20A2, PDGFB, PDGFRB, and XPR1 ) have been reported in patients with PFBC. Of these, point mutations or small deletions in SLC20A2 are most common. Thus far, only one large deletion covering entire SLC20A2 and several smaller, exonic deletions of SLC20A2 have been reported. The aim of this study was to identify the causative gene defect in a Finnish PFBC family with three affected patients. Materials and methods: A Finnish family with three PFBC patients and five unaffected subjects was studied. Sanger sequencing was used to exclude mutations in the coding and splice site regions of SLC20A2, PDGFRB, and PDGFB . Whole‐exome (WES) and whole‐genome sequencing (WGS) were performed to identify the causative mutation. A SNP array was used in segregation analysis. Results: Copy number analysis of the WGS data revealed a heterozygous deletion of ~578 kb on chromosome 8. The deletion removes the 5′ UTR region, the noncoding exon 1 and the putative promoter region of SLC20A2 as well as the coding regions of six other genes. Conclusions: Our results support haploinsufficiency of SLC20A2 as a pathogenetic mechanism in PFBC. Analysis of copy number variations (CNVs) is emerging as a crucial step in the molecular genetic diagnostics of PFBC, and it should not be limited to coding regions, as causative variants may reside in the noncoding parts of known disease‐associated genes.